2007
DOI: 10.1002/pmic.200601011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers associated with the development of hepatocellular carcinoma in CuZn superoxide dismutase deficient mice

Abstract: To identify biomarkers associated with the development of hepatocellular carcinoma (HCC) in CuZn superoxide dismutase (CuZnSOD, Sod1) deficient mice, 2-DE followed by MS analysis was carried out with liver samples obtained from 18-month-old Sod1−/− and +/+ mice. The intra-cellular Ca binding protein, regucalcin (RGN), showed a divergent alteration in Sod1−/− samples. Whereas elevated RGN levels were observed in −/− samples with no obvious neoplastic changes, marked reduction in RGN was observed in −/− samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 40 publications
4
30
0
Order By: Relevance
“…1). The decreased abundance of MUP in murine hepatocellular carcinoma (13) is similar to the findings in our study, possibly indicative of comparable pathological mechanisms in hepatocellular carcinoma and chronic schistosomiasis. Interest-ingly, the pattern of MUP isoforms differs between male and female mice (7), and this protein is similar to human epididymisspecific lipocalin 9 (30); whether lipocalin 9 correlates with degree of pathology in human schistosomiasis merits investigation.…”
Section: Discussionsupporting
confidence: 89%
“…1). The decreased abundance of MUP in murine hepatocellular carcinoma (13) is similar to the findings in our study, possibly indicative of comparable pathological mechanisms in hepatocellular carcinoma and chronic schistosomiasis. Interest-ingly, the pattern of MUP isoforms differs between male and female mice (7), and this protein is similar to human epididymisspecific lipocalin 9 (30); whether lipocalin 9 correlates with degree of pathology in human schistosomiasis merits investigation.…”
Section: Discussionsupporting
confidence: 89%
“…One of the most frequently used mouse models of oxidative stress and ageing is the copper-zinc Sod fully deficient mouse (Sod1 K/K ). Sod1 knockout animals (Sod1 K/K ) exhibit an elevation in the levels of various markers of oxidative stress (Elchuri et al 2005, Muller et al 2006, Perez et al 2009), but otherwise appear relatively normal under standard laboratory conditions (Reaume et al 1996, Elchuri et al 2007. The fertility of female Sod1 K/K mice is greatly reduced, but three independent studies have reported that males are fully fertile when mated with C57BL/6 females (Ho et al 1998, Matzuk et al 1998, Tsunoda et al 2012, the genetic background on which this knockout is usually maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Of the three genes that encode SOD in mammals, SOD1 is present largely in the cytoplasm and partly in the intramembrane space of mitochondria (OkadoMatsumoto and Fridovich 2001). Among the multiple phenotypes, SOD1-knockout (KO) mice show a shortened life span with increasing incidence of hepatocarcinogenesis (Elchuri et al 2005;Busuttil et al 2005;Elchuri et al 2007) and abnormal lipid metabolism (Hadjur et al 2001;Uchiyama et al 2006;Wang et al 2012). The body weights of SOD1-KO mice are low compared to that of WT mice (Iuchi et al 2007), which is partly attributable to small amounts of visceral fats due to impaired lipid adsorption by the intestine (Kurahashi et al 2012).…”
mentioning
confidence: 99%